Out-of-pocket expenditure on healthcare amongst households of an urban village in Delhi - Singh, Suraj P.; Khokhar, Anita (International Journal Of Community Medicine And Public Health, 2023)
Background: Poor urban households residing in an unplanned overcrowded settlement, are at a higher risk of morbidities and healthcare expenditure which can be impoverishing. Effective assessment of healthcare expenditure of households living in an urban village is needed to mitigate and protect the vulnerable households from catastrophic health expenditure. The objective of the study was to find out the mean out-of-pocket expenditure on healthcare, and catastrophic health expenditure amongst households of an urban village of Delhi. Methods: This 18-month duration cross-sectional study was carried out in an urban village of Delhi, Aliganj amongst households residing for the last one year. A sample size of 188 was statistically calculated, and households were selected using systematic random sampling. A pre-designed, pre-tested, semi-structured and interviewer administered questionnaire was used in Hindi to elicit and record information. Data was recorded and coded in MS Excel, and analysis was done using licensed SPSS v.26. Tables was generated, and cross-tables were used to assess statistical association with Chi-square or Fischer Exact tests, as required. Multivariate logistic regression was applied to the variables found having a statistically significant association on cross-tables (p<0.05). Results: The mean out-of-pocket expenditure borne by a household was INR 20,125.5 (SD± 50,772.3), with a median expenditure of INR 1800. Eighty percent of OOPE was incurred as direct expenditure and 56% was spent in private health facilities. Conclusions: The households of an urban village of Aliganj, Delhi, have high out-of-pocket expenditure (60.6%), and catastrophic health expenditure (22.9%).